French Foreign Policy and Financial Institutions in the Process of the Consolidation of Ottoman Foreign Debts - Semih Sefer (Tarih Dergisi)
This study aims to examine some of the issues discussed in the literature on international foreign debt contracts within the framework of the Consolidation of Ottoman Foreign Debts Project (Tevhîd-i Düyûn). At the early years of the twentieth century, when the compliance of external debt contracts with the rules of international law was being debated, one of the issues questioned was the situation between states and their citizens who were creditors of another state. The main problematics under examination are as follows: the conditions under which states could intervene in contracts, the expectations of bondholders from their governments, and the points where the interests of the two sides conflicted and met. The answers to these questions will be sought in France's influence on the restructuring of the Ottoman foreign debt and its relationship with French bondholders.